2014
DOI: 10.15403/jgld.2014.1121.233.lkb
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Esophageal and Lower Esophageal Sphincter Motility with Healthy Aging

Abstract: Background & Aims: Swallowing difficulties become increasingly prevalent in older age. Differences exist in lower esophageal sphincter (LES) function between older and younger patients with dysphagia, but the contribution of aging per se to these is unclear.Methods: Esophageal motor function was measured using high resolution manometry in older (aged 81±1.7 yrs) and younger (23±1.7 yrs) asymptomatic healthy adults. After baseline recording, motility was assessed by swallowing boluses of liquid (right later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
3
24
0
1
Order By: Relevance
“…Our findings demonstrating reduced swallow-induced EGJ relaxation in healthy aging, is consistent with a previous study by Besanko et al[18], which showed decreased swallow-induced relaxation, as measured through the IRP4, in healthy older adults over eighty years. Likewise, Jung et al[31] also showed a significant correlation of IRP4 with age and aging.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings demonstrating reduced swallow-induced EGJ relaxation in healthy aging, is consistent with a previous study by Besanko et al[18], which showed decreased swallow-induced relaxation, as measured through the IRP4, in healthy older adults over eighty years. Likewise, Jung et al[31] also showed a significant correlation of IRP4 with age and aging.…”
Section: Discussionsupporting
confidence: 93%
“…We have recently described changes in the distal esophagus of individuals aged over eighty years, including reduced peristaltic vigor and clearance[15], as well as reduced EGJ relaxation in both healthy and dysphagic aged individuals[16-18]. Both reduced clearance and decreased EGJ relaxation mimic the circumstances under which a reduced bolus flow time had previously been described by Lin et al[13,14] and it would thus be of value to further assess EGJ function in the aged population, using the BFT.…”
Section: Introductionmentioning
confidence: 99%
“…Our data show that age was inversely correlated with DL, but not with any other parameters. In contrast, a study using 16‐channel water‐perfused HRM in 10 older and 10 young asymptomatic healthy participants showed that overall esophageal function was well preserved . Considering that most countries’ populations are aging, the impact of age‐related changes on normal esophageal function should be carefully assessed.…”
Section: Discussionmentioning
confidence: 98%
“…One thousand seven hundred fourteen patients were included, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] of whom 1284 were symptomatic and 430 asymptomatic individuals. The sequence of the position assumed during HRM was described in almost all studies.…”
Section: High-resolution Manometry Protocolsmentioning
confidence: 99%
“…The sequence of the position assumed during HRM was described in almost all studies. Some authors referred that the exam was started in the supine position and the subsequent series of swallows was performed in the sitting/upright position; 12,14,15,18,19,24 other referred the opposite. 16,20,22,23 both to the upright or supine position in the studies by Zhang et al 17,21 and Misselwitz et al 26 Only 5 studies 14,16,17,19,24 reported the inclination assumed by the patient during the exam: between 0° and 20° for the supine position and between 75° and 90° for the upright/sitting position.…”
Section: High-resolution Manometry Protocolsmentioning
confidence: 99%